Factors Affecting Hemodialysis Patients' Satisfaction with Their Dialysis Therapy - M. Al Eissa; M. Al Sulaiman; M. Jondeby; A. Karkar; M. Barahmein; F. A. M. Shaheen; A. Al Sayyari (International Journal of Nephrology)
Aim. To assess the degree of satisfaction among hemodialysis patients and the factors influencing this satisfaction. Methods. Patients were recruited from 3 Saudi dialysis centers. Demographic data was collected. Using 1 to 10 Likert scale, the patients were asked to rate the overall satisfaction with, and the overall impact of, their dialysis therapy on their lives and to rate the effect of the dialysis therapy on 15 qualities of life domains. Results. 322 patients were recruited (72.6% of the total eligible patients). The mean age was 51.7 years (±15.4); 58% have been on dialysis for >3 years. The mean Charlson Comorbidity Index was 3.2 (±2), and Kt/V was 1.3 (±0.44). The mean satisfaction score was (7.41 ± 2.75) and the mean score of the impact of the dialysis on the patients' lives was 5.32 ± 2.55. Male patients reported worse effect of dialysis on family life, social life, energy, and appetite. Longer period since the commencement of dialysis was associated with adverse effect on finances and energy. Lower level of education was associated with worse dialysis effect on stress, overall health, sexual life, hobbies, and exercise ability. Conclusion. The level of satisfaction is affected by gender, duration on dialysis, educational level, and standard of care given.